"What about special ed?": Barriers and enablers for teaching with technology in special education. (February 2023) - Starks, Allison C.; Reich, Stephanie M.
Abstract: Technology integration in school is an increasingly important equity issue, but little is known about how technology is used for teaching the 7 million K-12 special education students in the US (NCES, 2019). Though special education is often overlooked in technology integration research, what does exist suggests that technology use in schools often exacerbates opportunity gaps for students with disabilities (Ciampa, 2017; Dolan, 2016; Shaheen & Watulak, 2019). The rapid shift to remote learning during the COVID-19 pandemic offers an opportunity to better explore enablers and barriers to technology-enabled learning for special education (SPED) because of the widespread reliance on technology for teaching and learning. Using in-depth interviews (N = 20) with special educators during remote learning, the present study seeks to (1) describe important enablers and barriers for SPED teacher use of technology in K-12 before and during remote learning, (2) understand how structural, teacher, and student-level factors influence SPED teachers' opportunities for teaching with technology, and (3) highlight emerging problems for SPED populations in technology-enabled learning. Results suggest that the most prominent enablers and barriers for technology use in special education are structural (e.g., decision-making around teacher training and technology resources, structures for student digital literacy training), but manifest at the teacher and student levels. SPED teachers described significant barriers to providing accessible technology-enabled instruction, largely due to school-based structures for resource allocation, student digital literacy training, teacher training, decision-making for technology, SPED job roles, and home-school communication. Recommendations are made for providing high-quality digital learning for all students, especially students with diverse learning needs. Highlights: Special education technology integration is limited by district and school structures. SPED students lacked access to devices, internet, software and digital literacy skills. SPED teachers need more technology training and time to use technology. Special education is often left out of school decision making about technology. Home-school communication practices should be inclusive of language and device access.